2021
DOI: 10.3171/2020.10.focus20620
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of endoscope-assisted microsurgery in the management of pediatric brain tumors

Abstract: OBJECTIVEMicrosurgical and endoscopic techniques are vastly utilized in brain tumor surgery. Combining both techniques in the same procedure has different forms and applications. The aim of this work was to discuss the usefulness and describe the technical benefits of endoscope-assisted microsurgery (EAMS) in treating pediatric brain tumors in various anatomical locations.METHODSThe medical records of 106 children who had undergone EAMS for brain tumors at Children’s Cancer Hospital Egypt (CCHE-57357) between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Micro-endoscopic surgery expands the field of view in deeper regions of the body [ 9 , 10 , 11 ]; however, various issues have been pointed out [ 10 , 16 , 18 ], including the difficulty in simultaneously observing both the endoscopic and microscopic fields of view, complexity of setting up the monitoring equipment in the operating room [ 12 , 18 ], interference of the endoscope itself and endoscope fixation devices with surgical operations [ 12 , 16 ], and tissue damage during the insertion and removal of the equipment [ 10 ]. A search on PubMed showed that many studies on the advantages of MES have been published since 1998.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Micro-endoscopic surgery expands the field of view in deeper regions of the body [ 9 , 10 , 11 ]; however, various issues have been pointed out [ 10 , 16 , 18 ], including the difficulty in simultaneously observing both the endoscopic and microscopic fields of view, complexity of setting up the monitoring equipment in the operating room [ 12 , 18 ], interference of the endoscope itself and endoscope fixation devices with surgical operations [ 12 , 16 ], and tissue damage during the insertion and removal of the equipment [ 10 ]. A search on PubMed showed that many studies on the advantages of MES have been published since 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Microsurgery in the field of neurosurgery has been performed since the 1950s. The usefulness and limitations of the “temporary simultaneous use of an endoscope during microscopic surgery” (herein, micro-endoscopic surgery (MES)) were not reported until the 1990s; it has been used for deep and back-surface observation of anatomical objects [ 9 , 10 , 11 , 12 , 13 ]. For example, endoscope-assisted observation of the perforating branch behind an aneurysm, which helps obtain the necessary information for clipping that cannot be observed with a MS alone, is possible [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Over time, the operating microscope and endoscopic systems have become invaluable optical technologies with neurosurgical procedures benefiting from their utilization sometimes even in a complementary manner depending on the specific surgery and stage of the procedure. 3 The neurosurgical application of the exoscope combines some of the advantages of the operating microscope and the endoscope. 4 Surgeons have praised the exoscope for improved surgeon ergonomics.…”
mentioning
confidence: 99%
“…2 Over time, the operating microscope and endoscopic systems have become invaluable optical technologies with neurosurgical procedures benefiting from their utilization sometimes even in a complementary manner depending on the specific surgery and stage of the procedure. 3…”
mentioning
confidence: 99%